A tributação como instrumento de redução da desigualdade econômica no estado social: críticas à atual progressividade do imposto de renda - Ramalho, Ana Paula Ferreira de Almeida Vieira (2020)
In Brazil there is an intense social inequality on the economic side, which is aggravated by the fiscal injustice, that marks the Brazilian tax system as regressive, as it places more burden on the less favored classes and increases the concentration of wealth in a small portion of the population. The regressive character of Brazilian taxation is characterized by the greater composition of the tax burden from indirect taxes (incidents on consumption of goods and services) in relation to the right taxes (incidents on income, capital and equity), so that the less favored population ends up more consuming their income with taxes, in relation to the richest portion of the population. The Brazilian tax burden, despite the prevailing idea in common sense, is not high, as it is around 33% of GDP, a percentage similar to the member countries of the Organization for Economic Cooperation and Development (OECD), but aggravates inequalities by their greater composition of the consumption of goods and services in relation to income, equity and capital. In the country, in the 1980-1990s, following mainly the political and economic orientations of the Ronald Reagan and Margaret Thatcher governments in the United States and the United Kingdom, there was a reduction in the progressivity of income tax, in view of the ideas reducing income and capital taxation. In the country, in the 1980- 1990s, following mainly the political and economic orientations of the Reagan and Thatcher governments in the United States and the United Kingdom, there was a reduction in the progressivity of income tax, in view of the ideas reducing income and capital taxation. Thus, the purpose of the research is to foster the debate on taxation as a means of reducing economic inequality in the Social State, and the criticism of the current progressivity of income tax is the starting point for changes in infra-constitutional legislation, in order to increase taxation. on income and reduce on consumption to better combine efficiency and fairness in taxation. At the same time, the constitutionally foreseen strengthening of the Social State is urgent, as it is one of the ways to promote economic and social development, as investment in the provision of public services related to social rights, such as education, health , sanitation, social assistance, etc., provided for in art. 6 of the Federal Constitution, allows access to such rights and the improvement of the population's life. In this way, the tax system must be in line with the constitutional objectives of building a free, just and solidary society; fight against poverty and reduction of social and regional inequalities and national development, according to art. 3 of the Federal Constitution, and not only based on the ideas of economic growth and fiscal neutrality. From the methodological point of view, it is a bibliographical, exploratory, descriptive and interpretative research, of qualitative nature through bibliographic and documentary analysis.